Wood Cellular Dendroclimatology: Testing New Proxies in Great Basin Bristlecone Pine - Ziaco, Emanuele; Biondi, Franco; Heinrich, Ingo (Frontiers in Plant Science, 2016)
Dendroclimatic proxies can be generated from the analysis of wood cellular structures, allowing for a more complete understanding of the physiological mechanisms that control the climatic response of tree species. Century-long (1870-2013) time series of anatomical parameters were developed for Great Basin bristlecone pine (Pinus longaeva D.K. Bailey) by capturing strongly contrasted microscopic images through a Confocal Laser Scanning Microscope. Environmental information embedded in wood anatomical series was analyzed in comparison with ring-width series using measures of empirical signal strength. Response functions were calculated against monthly climatic variables to evaluate climate sensitivity of cellular features (e.g. lumen area; lumen diameter) for the period 1950-2013. Calibration-verification tests were used to determine the potential to generate long climate reconstructions from these anatomical proxies. A total of eight tree-ring parameters (two ring-width and six chronologies of xylem anatomical parameters) were analyzed. Synchronous variability among samples varied among tree-ring parameters, usually decreasing from ring width to anatomical features. Cellular parameters linked to plant hydraulic performance (e.g. tracheid lumen area and radial lumen diameter) showed empirical signal strength similar to ring-width series, while noise was predominant in chronologies of lumen tangential width and cell-wall thickness. Climatic signals were different between anatomical and ring-width chronologies, revealing a positive and temporally stable correlation of tracheid size (i.e. lumen and cell diameter) with monthly (i.e. March) and seasonal precipitation. In particular, tracheid lumen diameter emerged as a reliable moisture indicator and was then used to reconstruct total March-August precipitation from 1870 to 2013. Wood anatomy holds great potential to refine and expand dendroclimatic records by allowing estimates of plant physiological adaptations to external stressors. Integrating xylem cellular features with ring-width chronologies can widen our understanding of past climatic variability (including annual extreme events) and improve the evaluation of long-term plant response to drought, especially in connection with future warming scenarios.